A METHOD FOR CREATING A WEB PLATFORM TO DEVELOP PUPILS’ ALGORITHMIC THINKING IN PROGRAMMING (International Conference on Modern Science and Scientific Studies, 2025)
This article presents the problems of forming students' algorithmic thinking in programming. Also, the stages of creating a web platform designed to form students' algorithmic thinking in the field of programming are given.